2019
DOI: 10.5334/gjgl.846
|View full text |Cite
|
Sign up to set email alerts
|

Identifying agents of change: Simplification of possessive marking in Abui-Malay bilinguals

Abstract: This paper investigates variation in possessive marking in Abui, a language spoken in a minority bilingual community in eastern Indonesia. Abui youngsters grow up acquiring both Abui (Papuan) and Alor Malay (Austronesian), but only become active speakers of Abui when they reach adolescence. Due to this delay, their Abui is expected to show signs of both imperfect acquisition and contact-induced effects. This language background makes them an interesting population on which to carry out a cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Using context-free German sentences like (15a-d) in a speeded acceptability judgment and an implicit reading experiment, they found that (i) the L1-Spanish participants, as expected, showed less sensitivity than the L1-English group towards possessor-possessive mismatch as displayed in (15c-d); 12 (ii) high L2 proficiency may have helped L1-Spanish/L2-English in La-German but did not influence the performance of L1-English/L2-Spanish participants; (iii) contrary to their expectations, gender mismatch between possessive and possessee (Mutter 'mother'), as displayed in (15b,c) did not affect the L1-Spanish learners' performance in any significant way. The observation that L2 learners have difficulties deploying L2 constraints on possessives that are not present in their L1 is corroborated by Helland (2017), Pitz et al (2017) and Saad et al (2019) with respect to the structuresensitive binding constraints (Condition A vs. B) that characterize reflexive vs. irreflexive possessive markers.…”
Section: Osla Volume 12(2) 2021mentioning
confidence: 81%
See 1 more Smart Citation
“…Using context-free German sentences like (15a-d) in a speeded acceptability judgment and an implicit reading experiment, they found that (i) the L1-Spanish participants, as expected, showed less sensitivity than the L1-English group towards possessor-possessive mismatch as displayed in (15c-d); 12 (ii) high L2 proficiency may have helped L1-Spanish/L2-English in La-German but did not influence the performance of L1-English/L2-Spanish participants; (iii) contrary to their expectations, gender mismatch between possessive and possessee (Mutter 'mother'), as displayed in (15b,c) did not affect the L1-Spanish learners' performance in any significant way. The observation that L2 learners have difficulties deploying L2 constraints on possessives that are not present in their L1 is corroborated by Helland (2017), Pitz et al (2017) and Saad et al (2019) with respect to the structuresensitive binding constraints (Condition A vs. B) that characterize reflexive vs. irreflexive possessive markers.…”
Section: Osla Volume 12(2) 2021mentioning
confidence: 81%
“…OSLa volume 12(2) 2021 Saad et al (2019) investigated how well multilingual speakers whose first (majority) language (Austronesian Alor Malay) has binding-neutral 3 rd person possessive marking master the distinction between reflexive and irreflexive 3 rd person possessive marking in their second (minority) language (Indonesian Abui). They found that (pre-)adolescents did not fully master the distinction, whether in production or comprehension, and that the tendency was to overgeneralize the irreflexive prefix to reflexive contexts rather than the other way around, arguably because the former, being less restricted, is considerably more frequent in natural discourse.…”
Section: Lexical Interference In Non-native Resolution Of Possessives?mentioning
confidence: 99%
“…Abui is the largest indigenous Papuan (TAP) language spoken on the islands of Alor and Pantar. The variety studied here is the Takalelang dialect, which is also the most well documented and described one (Delpada 2016:201;Kratochvíl 2007Kratochvíl , 2011Kratochvíl , 2014aPerono Cacciafoco et al 2015;Saad 2020a;Saad et al 2019).…”
Section: Sociolinguistic Settingmentioning
confidence: 91%
“…The variation found in the results of the production task were used to identify four linguistic variables which could potentially differ across age-groups and to study how significant they were. For example, one variable was the use of a dedicated reflexive possessor affix in possessed object NPs, versus using a different, more general possessive affix in such contexts (Saad, Klamer, and Moro 2019;Saad 2020). As a second step, it was investigated whether the production of these variable features differed from their comprehension.…”
Section: Data Types Collectedmentioning
confidence: 99%